Muscle strength and stiffness in resistance exercise: Force transmission in tissues. Issue 3 (July 2017) - Chaudhry, Hans; Bukiet, Bruce; Anderson, Ellen Z.; Burch, Jared; Findley, Thomas
Summary: Physical therapists and osteopaths want to know the quantitative force transmitted in the tissues during resistance exercise and also the relationship between tissue strength and the specific type of resistance exercise of the skeletal muscles. This paper uses the strain energy function for large deformations associated with the active and passive response of transversely isotropic skeletal muscle tissue to evaluate muscle strength and force transmitted in tissues during resistance exercises for the quadriceps muscle at the knee during isometric training exercise at different knee angles in vivo. It is found that after an exercise program, the muscle stiffness is halved when the bending angle of the knee increases from 50° to 100°. The muscle strength generated is marginally greater at 100° than at 50°. The stress transmitted in the lateral direction for 100° bending is double that for 50°.